Exploring the mechanism of coordinated development with multi-source data fusion: a case study in Beijing-Tianjin-Hebei Region, China - Li, Shujing; Wei, Yukun (Frontiers in Ecology and Evolution, 2023)
Measuring the degree of regional coordinated development and analyzing the factors affecting regional coordinated development are of great significance for assessing the status of regional coordinated development and formulating regional coordinated development strategies. The advancement of remote sensing data and big data provide the possibility to measure the degree of regional coordinated development on a more precise scale. The aim of this study is to use multiple sources of data to construct the evaluation indicator system of coordinated development level and to analyze the mechanism of regional development. All the 200 counties (districts) in Beijing-Tianjin-Hebei Region are selected as the study area. By measuring the level of coordinated development of 200 county units in Beijing-Tianjin-Hebei region from 2012 to 2017, it is found that although the synergy degree at the county level of Beijing, Tianjin and Hebei is increased, the overall regional synergy degree is still at a low level. The spatial panel model is further used to analyze the factors that influence the coordinated development of all counties. The conclusion is that with the promotion of the Beijing-Tianjin-Hebei coordinated development policy, the excessive government intervention, and the imbalance of market allocation in the past in Beijing-Tianjin-Hebei region have been alleviated. However, the weaknesses in the process of the Beijing-Tianjin-Hebei coordinated development are still obvious. The population density and urban size have become the constraints in the process of coordinated development. The degree of opening to the outside world and the investment in the ecological environment construction is still far from enough. These findings enable us to have a clearer assessment of the level of coordinated development and a deeper understanding of the influence mechanism of the regional development in Beijing-Tianjin-Hebei region. Furthermore, this study might benefit regional development strategy research.